Internet and Its Contributions to Library Services - Yaşar Çelik (Türk Kütüphaneciliği)
This paper examines the major Internet services such as email, telnet and ftp and describes various information discovery and retrieval tools such as gopher, WAIS, and WWW. It also discusses the contributions of the Internet to library and information services.